Foundations of physical education, exercise science, and sport - Wuest, Deborah A. (McGrawHill, 2009)
Integrating the traditional presentation of the nature, scope, philosophy, and history of physical education and sport with the growing career opportunities available within this dynamic field, this text addresses the challenges and the future of the discipline. It emphasizes preparation for a diversity of careers, addressing areas such as teaching, coaching, exercise leadership, athletic and personal training, sport management, and sport media.